2002
DOI: 10.2337/diabetes.51.5.1580
|View full text |Cite
|
Sign up to set email alerts
|

The Early Natural History of Nephropathy in Type 1 Diabetes

Abstract: Renal structural abnormalities are known to precede the development of proteinuria, hypertension, and reduced renal function in patients with type 1 diabetes. The determinants of these early structural abnormalities are, however, largely unknown. The International Diabetic Nephropathy Study (IDNS) has recruited 243 children and adults (aged 10 -40 years) in Montreal, Minneapolis, and Paris to identify and quantify these determinants. All study subjects were normotensive and had normal-to-high glomerular filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
207
4
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(235 citation statements)
references
References 37 publications
22
207
4
2
Order By: Relevance
“…Moreover, these patients were relatively young and had a relatively short duration of diabetes. Nonetheless, consistent with our previous reports [13,20], glomerular structure was abnormal in both groups, although Vv(Mes/glom) did not exceed normal in the JGA T-cell positive group. However, there was no difference in GBM width or Vv(Mes/glom) between the two Type 1 diabetic groups.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, these patients were relatively young and had a relatively short duration of diabetes. Nonetheless, consistent with our previous reports [13,20], glomerular structure was abnormal in both groups, although Vv(Mes/glom) did not exceed normal in the JGA T-cell positive group. However, there was no difference in GBM width or Vv(Mes/glom) between the two Type 1 diabetic groups.…”
Section: Discussionsupporting
confidence: 93%
“…The present study was done to determine whether these prior observations [17] could be confirmed and whether demographic, clinical or renal morphometric differences exist between Type 1 diabetic patients with and without JGA T-cell infiltration. This study was possible because of the large number of renal biopsies available from the NHDN study, ranging from young patients with a relatively brief duration of diabetes to older patients with diabetes for as long as 20 years [19,20]. The study included two highly polarized groups, one clearly positive and the other clearly negative for JGA T-cell infiltration in renal biopsy tissues containing at least seven glomeruli or four JGA's.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations